The Effect of Teaching Styles on Student-Teacher Interaction in a University: A Gender Based Analysis - Asma Seemi Malik; Shehla A Yasin; Amjad Mahmood; Madeeha Tariq, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Globally, teaching is one of the most renowned professions as teachers play an important role in the character building of not only the students but the people of any area. The present study aimed to explore the gender difference in teaching styles and how it affects the interaction between students and teachers; how it enhances the motivation and discipline of students. It also attempted to explore whether students feel that differences in teaching styles are effective to enhance their learning and academic performance. The students both male and female were selected through purposive sampling techniques. In-depth interviews were conducted with the help of a structured interview protocol by Ya-Ching Chang (2010). The participants (n=12) included 6 boys and 6 girls within the age group of 18-24 years. The sample was chosen from the public university of Lahore. The thematic analysis was used to bring out the emerging themes. The study identified three major themes. The participants perceived the issues of partiality and punctuality among teachers. Both male and female participants mostly perceived male faculty members to be more empathetic and maintained better discipline among students and motivated the students to learn.